Survival Growth Rate and Feed Efisiensi of Catfish (Clarias batracus) with Addition of Spirulina to the Concrete Pond Media - Sri Murtini; Rudiansyah Rudiansyah; Neksidin Neksidin; Anna Heirina; Dwi Retno Wulandari; Yeni Novita (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The addition of spirulina platensis to fish feed can increase fish growth and fish immunity. This research was conducted using a completely randomized design method with three treatments and three replications. Treatment A (control), Treatment B (addition 6g of Spirulina platensis/1kg of feed), Treatment C (addition 12g of Spirulina platensis/1kg of feed). The results showed that treatment C had better results than other treatments, where the daily growth rate was 3.29%, the feed efficiency was 58.96%, and the survival rate was 100%. This study showed that the addition of 12g of Spirulina platensis was able to increase survival growth rate and feed efficiency of catfish for 30 days of rearing, this addition was still possible to increase the dose of spirulina to the most appropriate dose, considering that the addition of the difference with treatment B gave significant results.